Assessment of the Effectiveness of the Parenting Intervention Programme “Intelligent Families”: A Randomised Controlled Study - Ana Martinez-Pampliega; Antonio Ortuño; Estefania Mónaco (Social Sciences)
This study presents and analyses the effectiveness of the programme “Intelligent Families” aimed at promoting the development of parenting skills in parents within the framework of positive parenting. The popularity of attachment- and emotion-based interventions seems to have grown among clinicians, researchers and parents. However, in Spain, these programmes are practically non-existent or do not provide evidence of their effectiveness. A randomised experimental study with two groups (experimental and control) and a longitudinal design (pre, post and follow-up) was conducted to test the programme’s impact on parenting skills. The sample comprised 637 Spanish parents. Two moderating variables were considered: the modality (face-to-face or online) and the length of the intervention (2 or 4 sessions). The experimental group significantly increased their empathic authority, established rules with confidence and sensitivity, and could negotiate in everyday family conflicts. There were no differences according to the parent’s gender, the children’s age, or the intervention’s modality or duration. This study verified the effectiveness of the “Intelligent Families” intervention programme. The importance of developing and studying the effectiveness of preventive actions to promote families’ emotional well-being is discussed.